4(at+cx)^2+(2ct-2ax)^2
4(at+cx)^2+(2ct-2ax)^2
* 4*(a*t + c*x)^2 + (2*c*t - 2*a*x)^2 =
= 4*((a*t)^2 + 2*(a*t)*(c*x) + (c*x)^2) + ((2*c*t)^2 - 2*(2*c*t)*(2*a*x) + (2*a*x)^2) =
= 4*(a*t)^2 + 4*2*(a*t)*(c*x) + 4*(c*x)^2 + (2*c*t)^2 - 2*(2*c*t)*(2*a*x) + (2*a*x)^2 =
= 4*(a*t)^2 + 8*a*t*c*x - 2*(2*c*t)*(2*a*x) + 4*(c*x)^2 + 4*(c*t)^2 + 4*(a*x)^2 =
= 4*((a*t)^2 + (c*x)^2 + (c*t)^2 + (a*x)^2) =
= 4*((a^2)*t^2 + (a^2)*x^2 + (c^2)*t^2 + (c^2)*x^2) =
= 4*((a^2)*(t^2 + x^2) + (c^2)*(t^2 + x^2)) =
= 4*(a^2 + c^2)*(t^2 + x^2)
4·(a·t + c·x)^2 + (2·c·t - 2·a·x)^2=
=4·(a^2 + c^2)·(x^2 + t^2)
--------------------------------------------
(4·c^2·x^2 + 8·a·c·t·x + 4·a^2·t^2) + (4·a^2·x^2 - 8·a·c·t·x + 4·c^2·t^2) =
=4·a^2·x^2 + 4·c^2·x^2 + 4·a^2·t^2 + 4·c^2·t^2=
=4·(a^2·x^2 + c^2·x^2 + a^2·t^2 + c^2·t^2)=
=4·((a^2·x^2 + c^2·x^2) + (a^2·t^2 + c^2·t^2))=
=4·(x^2·(a^2 + c^2) + t^2·(a^2 + c^2))=
=4·(a^2 + c^2)·(x^2 + t^2)